Use of acids as additives in sugarcane silage - van Cleef, Eric HCB; Rêgo Anibal C; Patiño René M; Scarpino van Cleef, Flavia O; Ezequiel, Jane MB (Revista Colombiana de Ciencias Pecuarias, 2015)
Background: sugarcane silage often becomes a problem for the producers due to its high population of yeast and its high content of soluble carbohydrates. Objective: to evaluate the effect of formic and phosphoric acid on the chemical composition, fermentation characteristics, and digestibility of sugarcane silages. Methods: sugarcane was ensiled in experimental mini-silos. Five treatments were evaluated in the ensilage process (sugarcane added with 0.5 or 1% formic acid and 0.5 or 1% phosphoric acid, and a control treatment without additives). A completely randomized design was used. Results: the dry matter content of silages containing phosphoric acid was lower. Lower values of NDF, ADF, and hemicellulose were observed in the control and formic acid treatments. Conclusions: formic and phosphoric acids promote beneficial changes in the chemical composition of sugar cane silage.